Coagulant recovery from water treatment residuals: a review of applicable technologies - Keeley, James; Jarvis, Peter; Judd, Simon J. (Taylor and Francis, 2014)
Conventional water treatment consumes large quantities of coagulant and produces even greater volumes of sludge. Coagulant recovery (CR) presents an opportunity to reduce both the sludge quantities and the costs they incur, by regenerating and purifying coagulant before reuse. Recovery and purification must satisfy stringent potable regulations for harmful contaminants, while remaining competitive with commercial coagulants. These challenges have restricted uptake and lead research towards lower-gain, lower-risk alternatives. This review documents the context in which CR must be considered, before comparing the relative efficacies and bottlenecks of potential technologies, expediting identification of the major knowledge gaps and future research requirements.
Keywords: coagulant recovery; Donnan membrane; ultrafiltration; water treatment residuals; waterworks sludge